Polish Strategic Analyses – Review of 2017 Publications - WIŚNIEWSKI, Rafał (Przegląd Strategiczny, 2018)
The text is a review of selected articles from leading Polish academic journals dealing with the topic of international security. It aims to present the most important topics of current debate taking place in Polish strategic studies.